Money, banking and the foreign exchange market in emerging economies - Khemraj, Tarron; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2014)
'One of the fundamental features of the financial system in most small island developing countries is the existence of oligopolistic banking systems. While economists have, for some time now, been working on developing models to explain the behaviour of firms in such market structures, this book is unique as it applies these tools to monetary models of the banking system. In doing so, the text highlights many of the important differences between banking systems in small states and those in larger and more developed markets. Applied researchers, policymakers, students and teachers examining the behaviour of financial systems in small states would find the text quite useful, as it provides fairly accessible theoretical models supported by relevant data and econometric analysis.'--Winston Moore, The University of the West Indies. Despite the financial liberalization agenda of the mid-1980s, a system of bank oligopolies has developed in both large and small, open developing economies. Mainstream monetary theory tends to assume a capital markets structure and is therefore not well suited to an analysis of these economies. This book outlines a unique theoretical framework that can be used to examine monetary and exchange rate policies in developing economies or other economies in which banks dominate external finance. Giving the foreign exchange market a prominent role, this volume presents extensive econometric results and descriptive statistics to support core theoretical ideas, including both micro and macroeconomic models. Topics discussed include oligopoly market power, excess liquidity, bank concentration, interest rate spread and the implications of bank foreign exchange trading on exchange rate stability, foreign exchange rate regime choice and monetary management. Students and scholars of development economics, money and banking, and development finance will find this book a valuable resource, as will policy makers and others affiliated with central banks in developing economies.
Description based on online resource; title from title screen (viewed July 17, 2014).
Keywords: Finance -- Developing countries; Financial institutions -- Developing countries; Foreign exchange market -- Developing countries; Developing countries -- Economic conditions; Developing countries -- Economic policy; Electronic books